Sustainability in spanish energy companies. A proposal for indicators beyond taxonomy - Pérez-Alfonso, Lorena; Fuster-Navarro, Clara; Pallarés-Renau, María (Papeles de Europa, 2025)
This study analyzes the sustainability of the main energy companies in the IBEX 35: Acciona, Endesa, and Iberdrola. Through a qualitative analysis of the 2023 Non-Financial Information Statements, their commitment to sustainability is examined beyond the local Environmental Taxonomy Regulation by identifying new indicators. It is concluded that the main predictors are: a Long-term Action Plan or Strategy; activities aligned with the Sustainable Development Goals; Double Materiality; policies and analysis of environmental, social, and governance factors; reporting information on the company’s sustainable financing; and certificates that verify the reported information.